Innovation ecosystems: a meta-synthesis. Issue 4 (25th April 2018) - Ferasso, Marcos; Wunsch Takahashi, Adriana R.; Prado Gimenez, Fernando A.
Abstract : Purpose: This metasynthesis aims to build a theory on the concept of innovation ecosystem from the state of the art of qualitative case studies available in indexed scientific production using interpretive synthesis (Hoon, 2013 ). Design/methodology/approach: This research was conducted by the postulates of the metasynthesis method (Hoon, 2013 ) to generate theory from qualitative case studies. The authors retrieved 77 research papers from databases, of which 6 were used for synthesis purposes. Each selected research paper reported one or more cases, which were analyzed separately. At the final stage, a data synthesis was structured and the cases were crossed, which allowed the development of a schematic representation and a theoretical construction of the innovation ecosystem concept. The approach used in this research is a metatheoretical assumption from economics and management and ecology to explore the theoretical gap in the concept of innovation ecosystems. Findings: There is not yet a conceptual consensus on the term, which sometimes leads researchers to address partial or complementary concepts. The analysis identified constitutive elements of an innovation ecosystem that lead to structuring a framework of organic and dynamic interrelationships that a given organization has with various external organizations, allowing the creation of innovative products in a faster way. Research limitations/implications: This paper helps scholars and researchers consider a new metatheoretical perspective to analyze dynamics, constitutive elements and multilevels of an innovation ecosystem. Practical implications: For practitioners, this paper sheds lights on the importance of recognizing a systemic consideration of innovation ecosystems that falls in global relationships, industry dynamics and identification of main global–local actors/enablers to produce innovations internally at a given organization. Originality/value: The novelty of this paper lies in a more delineated definition and a schematic representation of an innovation ecosystem based on a global–local perspective of product creation and manufacturing and interactions that a given company has, regardless of the geographical location of its dispersed strategic partners.